Studies in Liocranidae (Araneae): redescriptions and transfers in Apostenus Westring and Brachyanillus Simon, as well as description of a new genus - Bosselaers, Jan (Zootaxa, 2009)
Three poorly known species of Apostenus Westring 1851 are redescribed: A. humilis Simon 1932, A. ochraceus Hadjissarantos 1940 and A. rutilius Simon 1897. A. rutilius is transferred to Agraecina Simon 1932 as A. rutilia new combination. The genus Brachyanillus Simon 1913 is synonymised with Cybaeodes Simon 1878 and B. liocraninus Simon 1913 is redescribed and transferred to Cybaeodes as C. liocraninus new combination. Arabelia pheidoleicomes gen. n., sp. n. (Araneae, Liocranidae) is described from Rhodos, Lesbos and Cyprus.